U-Pb detrital zircon geochronology of sedimentary rocks in NE Vietnam: Implication for Early and Middle Devoni-an Palaeogeography - P., Königshof; U., Linnemann; Phuong, Ta Hoa (Vietnam Journal of Earth Sciences, 2017)
Rocks of the Do Son Peninsula in NE Vietnam are mainly composed of Paleozoic siliciclastics. The overall sedimentary record represents fluvial to deltaic prograding deposits close to a shoreline. We present detrital zircon U-Pb analytical results from two samples, the Van Canh and the Van Huong Formations (east Red River Basin). Zircons were analyzed for U, Th, and Pb isotopes by LA-SF ICP-MS techniques. The youngest zircon of each formation provides maximum ages of sedimentation at 407.1 ± 9.5 Ma and 406.3 ± 4.0 Ma. The zircon cluster of both samples supports the postulated position of NE Vietnam close to the western Himalaya.ReferencesAnh H.T.H., Hieu P.T., Le Tu V., Choi S.H. and Yu Y., 2015. Age and tectonic implications of Paleoproterozoic Deo Khe Granitoids within the Phan Si Pan Zone, Vietnam. Journal of Asian Earth Sciences, 111, 781-791. Braddy S.J., Seldon P.A., Doan Nhat T., 2002. A new carcinosomatid eurypterid from the Upper Silurian of northern Vietnam. Palaeontology, 45, 897-915. Burrett C., 1974. Plate tectonics and the fusion of Asia. Earth and Planetary Science Letters, 21, 181-189. Burrett C. and Stait B., 1985. South East Asia as a part of Ordovician Gondwanaland-a palaeobiogeographic test of a tectonic hypothesis. Earth and Planetary Science Letters, 75, 184-190. Burrett C. and Stait B., 1987. China and Southeast Asia as part of the Tethyan margin of Cambro-Ordovician Gondwanaland. In: McKenzie, K. (Ed.), Shallow Tethys, 2. Balkema, Rotterdam, 65-77. Burrett C., Long J. and Stait B., 1990. Early-Middle Palaeozoic biogeography of Asian terranes derived from Gondwana. In: McKerrow, W., Scotese, C. (Eds.), Palaeozoic Palaeogeography and Biogeography. Geological Society Memoir, 12, 163-174. Burrett C., Duhig N., Berry R. and Varne R., 1991. Asian and south-western Pacific continental terranes derived from Gondwana and their biogeographic significance. Australian Systematic Botany, 4, 13-24. Burrett C., Zaw K., Meffre S., Lai C.K., Khositanont S., Chaodumrong P., Udchachon M., Ekins S. and Halpin J., 2014. The Configuration of Greater Gondwana - Evidence from LA ICPMS, U-Pb geochronology of detrital zircons from the Palaeozoic and Mesozoic of Southeast Asia and China. Gondwana Research, 26, 31-51. http://dx.doi.org/10.1016/j.gr.2013.05.020. Condie K., Belousova E., Griffin W. and Sircombe K., 2009. Granitoid events in space and time: constraints from igneous and detrital zircon age spectra. Gondwana Research, 15, 228-242. http://dx.doi.org/10.1016/j.gr2008.06.001. Faure M., Lepvier C., Nguyen V.V., Vu T.V., Lin W. and Chen Z., 2014. The South China block-Indochina collision: Where, when, and how? Journal of Asian Earth Sciences, 79, 260-274. Findlay R.H., 1997 The Song Ma anticlinorium, northern Vietnam: the structure of an allochthonous terrane containing an early Paleozoic island arc sequence. Journal of Asian Earth Sciences, 15, 453-464. Gerdes A. and Zeh A., 2006. Combined U-Pb and Hf isotope LA-(MC-) ICP-MS analysis of detrital zircons: comparison with SHRIMP and new constraints for the provenance and age of an Armorican metasediment in Central Germany. Earth and Planetary Science Letters, 249, 47-61. Hall R., 2009. The Eurasia SE Asian margin as a modern example of an accretionary orogen. In: Cawood, P.A., Kroner, A. (Eds.), Earth Accretionary Systems in Space and Time. The Geological Society London, Special Publications, 318, 351-372. Helmcke D., 1985. The Permo-Triassic “Paleotethys” in mainland Southeast Asia and adjacent parts of China. Geologische Rundschau, 74, 215-228. Hieu P.T., Chen F., Me L.T., Thuy N.T.B., Siebel W. and Lan T.G., 2012. Zircon U-Pb ages and Hf isotopic compositions from the Sin Quyen Formation: the Precambrian crustal evolution of northwest Vietnam. International Geology Review, 54(13), 1548-1561. Hieu P.T., Dung N.T., Thuy N.T.B., Minh N.T. and Pham M.I.N.H., 2016. U=Pb ages and Hf isotopic composition of zircon and bulk rock geochemistry of the Dai Loc granitoid complex in Kontum massif: Implications for early Paleozoic crustal evolution in Central Vietnam. Journal of Mineralogical and Petrological Sciences, 111(5), 326-336. Horstwood M.S.A., Košler J., Gehrels G., Jackson S.E., McLean N.M., Paton C., Pearson N.J., Sircombe K., Sylvester P., Vermeesch P., Bowring J.F., Condon D.J. and Schoene, B., 2016. Community-derived standards for LA-ICP-MS U-Th-Pb geochronology - uncertainty propagation, age interpretation and data reporting. Geostand Geoanalytical Research, 40, 311-332. Jackson S., Pearson N.J., Griffin W.L. and Belousova E.A., 2004. The application of laser ablation-inductively coupled plasma-mass spectrometry to in situ U-Pb zircon geochronology. Chemical Geology, 211, 47-69. Janvier P., Blieck A., Gerrienne P. and Tong-Dzuy T., 1987. Faune et flore de la Formation de Sika (Devonien inferieur) dans la peninsule de Do Son (Viet Nam). Bulletin du Museum National d’Histoire Naturelle Paris, 9, 291-301. Janvier P., Racheboeuf P., Nguyen Huu H. and Doan Nhat T., 2003. Devonian fish (Placodermi, Antiarcha) from the Tra Ban Island (Bai Tu Long Bay, Quang Ninh, Vietnam) and the question of the age of the Do Son Formation. Journal of Asian Earth Sciences, 21, 795-801. Janvier P. and Ta Hoa P., 1999. Les Vertebres (Placodermi, Galeaspida) du Devonien inferieur de la coupe de Lung Co-Mia Le, province de Ha Giang. Vietnam, avec des donnees complementaires sur les gisements a Vertebres du Devonien du Bac Bo oriental. Geodiversitas, 21, 33-67. Janvier P. and Tong-Dzuy T., 1998. The Silurian and Devonian vertebrates of Vietnam: a review. Journal of Geology (Hanoi), B11, 12, 18-28. Jones N.S., Fyfe J.A., Sewell R.T., Lai K.W. and Lee C.M., 1997. Devonian fluviodeltaic sedimentation in Hong Kong. Journal of Asian Earth Sciences, 15(6), 533-545. Komatsu T., Kato S., Hirata K., Takashima R., Orata Y., Oba M., Naruse H., Tha Hoa P., Nguyen P.D., Dang H.T., Doan T.N., Nguyen H.H., Sakata S., Kaiho K. and Königshof P., 2014. Devonian-Carboniferous transition containing a Hangenberg Black Shale equivalent in the Pho Han Formation on Cat Ba Island, northeastern Vietnam. Palaeogeography, Palaeoclimatology, Palaeoecology, 404, 30-43. http://www.doi: 10.1016/j.palaeo.2014.03.021. Königshof P., Narkiewicz K., Phuong Ta Hoa, Carmichael S. and Waters J., 2017. Events in the mid- Paleozoic: Examples from the eastern Paleotethys (Si Phai section, NE Vietnam). In: Mottequin B., Slavik L., Königshof P. (eds.) Climate change and biodiversity patterns in the mid-Palaeozoic - Proceedings-Volume IGCP 596/SDS Meeting Brussels (2015). Palaeobiodiversity and Palaeoenvironments, 97(3), 481-496. http://www.doi.10.1007/s12549-017-0272-5. Lantenois H., 1907. Note sur la Géologie de l’Indochine. Mémoires de la Société Géologique de France, 4, 1-56. Lee C.M., 1991. The discovery of Devonian Placodermi in Hong Kong and its significance. In: Chang M.M., Liu Y.H., Zhang G.R. (Eds.). Early Vertebrates and Related Problems of Evolutionary Biology. Science Press, Beijing, 131-138. Lepvrier C., Faure M., Nguyen Van V., Van Vu T., Lin W., Ta Trong T. and Ta Hoa P., 2011. North-directed Triassic nappes in Northeastern Vietnam (East Bac Bo). Journal of Asian Earth Sciences, 41, 56-68. Long J.A., Burrett C., Pham Kim N. and Janvier P., 1990. A new bothriolepid antiarch (Pisces, Placodermi) from the Devonian of Do Son Peninsula, northern Vietnam. Alcheringa, 14, 181-194. Ludwig K.R., 2001. Users Manual for Isoplot/Ex rev. 2.49: Berkeley Geochronology Center Special Publication, No.1a, 1-56. Metcalfe I., 1984. Stratigraphy, palaeontology and palaeogeography of the Carboniferous of Southeast Asia. Mémoires Société Géologiques France (New Series), 147, 107-118. Metcalfe I., 1998. Palaeozoic and Mesozoic geological evolution of the SE Asian region: multidisziplinary constraints and implications for biogeography. In: Hall R., Holloway J.D. (Eds.), Biogeography and Geological Evolution of SE Asia. Backhuys Publishers, Leiden, The Netherlands, 25-41. Metcalfe I., 2006. Palaeozoic and Mesozoic tectonic evolution and Palaeogeography of East Asian crustal fragments: the Korean Penninsula in context. Gondwanan Research, 9, 24-46. Metcalfe I., 2011. Tectonic framework and Phanerozoic evolution of Sundaland. Gondwana Research, 19, 3-21. http://dx.doi.org/10.1016/j.gr.2010.02.016. Morley C.K., Ampaiwan P., Thanudamrong S., Kuenphan N. and Warren J., 2013. Development of the Khao Kwang Fold and thrust belt: implications for the geodynamic setting of Thailand and Cambodia during the Indosinian Orogeny. Journal of Asian Earth Sciences, 62, 705-719. http://dx.doi.org/10.1016/j.seaes.2012.11.021. My Dung Tran, Junlai L.I.U., Xiaochun L.I. and My Cung Dang., 2016. Geology, Fluid Inclusion and Isotopic Study of the Neoproterozoic Suoi Thau Copper Deposit, Northwest Vietnam. Acta Geologica Sinica (English Edition), 90(3), 913-927. Nagy E.A., Maluski H., Lepvrier Q., Scharer U., Thi P.T. and Leyreloup A., 2001. Geodynamic significance of the Kontum Massif in Central Vietnam: Composite 40Ar-39Ar and U/Pb ages from the Palaeozoic to Triassic. Journal of Geology, 109, 755-770. Nam T.N., 1995. The Geology of Vietnam: A brief summary and problems. Geoscientific Reports, Shizuoka University, 1-10. Nam T.N., Toriumi M., Sano Y., Terada K. and Thang T.T., 2003. 2.9, 2.36, and 1.96 Ga zircons in orthogneiss south of the Red River shear zone in Viet Nam: evidence from SHRIMP U-Pb dating and tectonothermal implications. Journal of Asian Earth Sciences, 21(7), 743-753. Nguyen T.T.B., Hieu P.T., Hai T.T., Xuan N.T. and Cung D.M., 2014. Petrogenesis and zircon U-Pb ages of the Thien Ke granitic pluton in the Tam Dao region: Implications for early Paleozoic tectonic evolution in NE Vietnam. Journal of Mineralogical and Petrological Sciences, 109(5), 209-221. Nie Y.S., 1991. Paleoclimate and paleomagnetic constraints on the Paleozoic reconstructions of South China, North China and Tarim. Tectonophysics, 196, 279-309. Ogg J.G., Ogg G.M. and Gradstein F.M., 2016. A concise geologic time scale. Elsevier: 1-234. Racheboeuf P.R., Janvier P., Ta Hoa P., Vannier J. and Wang S.-Q., 2005. Lower Devonian vertebrates, arthropods and brachiopods from northern Vietnam. Geobios, 38, 533-551. Roger F., Leloup P.H., Jolivet M., Lacassin R., Trinh P.T., Brunel M. and Seward D., 2000. Long and complex thermal history of the Song Chay metamorphic dome (Northern Vietnam) by multi-system geochronology. Tectonophysics, 321, 449-466. Sengör A.M.C., Altiner D., Cin A., Ustaomer T. and Hsu K.J., 1988. Origin and assembly of the Tethyside orogenic collage at the expense of Gondwana Land. In: Audley Charles, M.G., Hallam, A. (Eds.), Gondwana and Tethys. Geological Society of London, Special Publications, 37, 119-181. Sircombe K.N., 2004. AGE DISPLAY: an EXCEL workbook to evaluate and display univariate geochronological data using binned frequency histograms and probability density distributions. Computers & Geosciences, 30, 21-31. Sláma J., Košler J., Condon D.J., Crowley J.L., Gerdes A., Hanchar J.M., Horstwood M.S.A., Morris G.A., Nasdala L., Norberg N., Schaltegger U., Schoene B., Tubrett M.N. and  Whitehouse M.J., 2008. Plešovice zircon - A new natural reference material for U-Pb and Hf isotopic microanalysis. Chemical Geology, 249, 1-35. Sone M. and Metcalfe I., 2008. Parallel Tethyan sutures in mainland Southeast Asia: new insights for the Palaeo-Tethys closure and implications for the Indosinian Orogeny. Comptes Rendu Geoscience, 340, 166-179. http://dx.doi.org/10.1016/j.crte.2007.09.008. Squire R., Campbell I., Allen C. and Wilson C., 2006. Did the Transgondwanan Supermountain trigger the explosive radiation of animals on Earth? Earth and Planetary Sciences Letters, 250, 116-133. Stacey J.S. and Kramers J.D., 1975. Approximation of terrestrial lead isotope evolution by a two-stage model. Earth and Planetary Science Letters, 26, 207-221. Tapponnier P., Lacassin R., Leloup P.H., Scharer U., Zhong D., Wu H., Liu X., Ji S., Zhang L. and Zhong J., 1990. The Ailao Shan - Red River metamorphic belt: Tertiary left lateral shear between Sundaland and South China. Nature, 343, 431-437. Tong-Dzuy, T. (Ed.), 1986. The Devonian of Vietnam. Science and Technics Publishing House, Hanoi, 141p (in Vietnamese).Tong-Dzuy T., Janvier P., Doan Nhat T. and Braddy S., 1994. New vertebrate remains associated with eu-rypterids from the Devonian Do Son Formation. logy (Vietnamese), Hanoi, A, 224, 1-11. Torsvik T. and Cocks R., 2009. The Lower Palaeozoic palaeogeographical evolution of the northeastern and eastern peri-Gondwanan margin from Turkey to New Zealand. In: Bassett, M. (Ed.), Early Palaeozoic Peri-Gondwana Terranes: New Insights from Tectonics and Biogeography. Geological Society, London Special Publications, 325, 3-21. http://dx.doi.org/10.1144/SP325.2 0305-8719/09/. Tri T.V. and Khuc V. (Eds.), 2011. Geology and Earth Resources of Viet Nam. Ministry of Nature Resources and Environment. General Department of Geology and Minerals of Vietnam, 634p. Ueno K. and Charoentitirat T., 2011. Carboniferous and Permian. In: Ridd M., Barber A., Crow M. (Eds.), The Geology of Thailand. Geological Society, London, 71-136. Usuki T., Lan C.-Y., Wang K-L. and Chiu H.-Y., 2013. Linking the Indochina block and Gondwana during the Early Paleozoic: Evidence from U-Pb ages and Hf isotopes of detrital zircons. Tectonophysics, 586, 145-159. Vu Van Tich, 2001. Petrologie et Geochronologie Ar-Ar du Bloc de Kontum (Vietnam). DEA University, Montpelier, p40. Wan Y., Liu D., Wang W., Song T., Kroner A., Dong C., Zhou H. and Yin X., 2011. Provenance of Meso-Neo Proteroizoic cover sediments at the Ming Tombs, Beijing, North China Craton: an integrated study of U-Pb dating and Hf isotopic measurement of detrital zircons and whole rock geochemistry. Gondwana Research, 20, 219-242. http://dx.doi.org/1016/j.gr.2011.02.009. Xun Z., Allen M.B., Whitham A.G. and Price S.P., 1996. Rift-related Devonian sedimentation and basin development in South China. Journal of Southeast Asian Earth Sciences, 14(1/2), 37-52. Yan D.P., Zhou M.F. and Wang Y.C., 2006. Structural and geochronological constraints on the Dulong-Song Chay tectonic dome in SE Yunnan (SW China) and northern Vietnam. Journal of Asian Earth Sciences, 28, 332-353. Yang S.P., Pan K., and Hou H.F., 1981. The Devonian System in China. Geological magazine, 118(2), 113-224. Yu J.H., Wang L.J., O`Reilly S.Y., Griffin W.L., Zhang M., Li C.Z. and Shu L.S., 2009. A Paleoproterozoic orogeny recorded in a long-lived cratonic remnant (Wuyishan terrane), eastern Cathaysia Block, China. Precambrian Research, 174, 347-363. Zhao G.C. and Cawood P.A., 2012. Precambrian Geology of China. Precambrian Research, 222(223), 13-54. Zhao X., Allen M.B., Whitham A.G. and Price S.M., 1996. Rift-related Devonian sedimentation and basin development in South China. Journal of Southeast Asian Earth Sciences, 14(1/2), 37-52. Zhu D.C., Zhao Z.D., Niu Y.L., Dilek Y. and Mo X.X., 2011. Lhasa terrane in southern Tibet came from Australia. Geology, 39, 727-730.